Intra-normativities in technologizing old age care work: Mobile record-keeping, remote homecare and social media use shaping good care - Saari, Eveliina; Levonius, Vilja; Koskela, Inka; Koivisto, Tiina; Känsälä, Marja (Human Technology, 2024)
Western societies tend to implement new technologies to elder care work to replace routines in order to make services more efficient and transparent as the population ages and public resources diminish. However, we have not paid enough attention to how care practitioners perceive their changed circumstances in elder care work. Drawing on the thematic interviews of 31 care practitioners in Finland, we analyzed how the emergence of mobile record-keeping during homecare visits, use of video visits in remote homecare and social media use in intensive service housing shaped what is perceived as good care. Leaning on empirical ethics of care approach we found that each elder care service context and its technology shape its own intra-normativities. Each intra-normativity brings different values into being in elder care, which impact on work practices and how the relations between care practitioners and clients, and with the wider public are enacted.